2006
DOI: 10.1016/j.neulet.2006.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies that recognize functional domains of hnRNPA1 implicate molecular mimicry in the pathogenesis of neurological disease

Abstract: As a model for molecular mimicry in neurological disease, we study people infected with human T-lymphotropic virus type 1 (HTLV-1) who develop HTLV-1 associated myelopathy/tropical spastic paraparesis (HAM/TSP), an immune-mediated disease of the central nervous system (CNS). In HAM/TSP, data suggests molecular mimicry is the result of cross-reactive antibodies between HTLV-1-tax and heterogeneous nuclear ribonucleoprotein A1 (hnRNP A1), a protein over-expressed in human CNS neurons. The hnRNP A1 epitope recogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 21 publications
1
45
0
1
Order By: Relevance
“…However, antibodies from patients with autoimmune diseases have been found to cross-react with hnRNP A1 (Lee et al, 2006), suggesting that the cross-reaction is some kind of molecular mimicry.…”
Section: Discussionmentioning
confidence: 99%
“…However, antibodies from patients with autoimmune diseases have been found to cross-react with hnRNP A1 (Lee et al, 2006), suggesting that the cross-reaction is some kind of molecular mimicry.…”
Section: Discussionmentioning
confidence: 99%
“…Trabajos previos han presentado evidencias de que la hnRNP A1 tiene una reactividad cruzada con anticuerpos monoclonales para la proteína tax p40 del HTLV-I, y muestran que el reconocimiento de este autoantígeno involucra dominios definidos de esta proteína nuclear (30,31). Las ribonucleoproteínas heterogéneas nucleares (hnRNPs) son las proteínas más abundantes del núcleo de células eucarióticas (32).…”
Section: Discussionunclassified
“…It has been shown that patients with MS and HAM/ TSP produce autoantibodies to the intracellular RNA binding protein heterogeneous ribonuclear protein A1 (hnRNP A1) 3, 5-7, 9, 11 . Recent data indicate that antibodies to both intra-neuronal and surface antigens are pathogenic 3,[5][6][7][8][9]11 . Thus, a procedure that allows for the study of intracellular antibody:protein interactions would lend great insight into disease pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to produce highly specific antibodies to target proteins has allowed for very precise biological questions to be addressed. Importantly, antibodies have been implicated in the pathogenesis of a number of human diseases including systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), paraneoplastic syndromes, multiple sclerosis (MS) and human T-lymphotropic virus type 1 (HTLV-1) associated myelopathy/tropical spastic paraparesis (HAM/ TSP) [1][2][3][4][5][6][7][8][9] . How antibodies cause disease is an area of ongoing investigation, and data suggests that interactions between antibodies and various intracellular molecules results in inflammation, altered cellular messaging, and apoptosis 10 .…”
mentioning
confidence: 99%